Variabilidade espacial e temporal de atributos agronômicos em pomar de pessegueiro - Terra, Viviane Santos Silva (2012)
The fruitculture is an important component of Brazilian agribusiness assuming prominence in the economy of the state of Rio Grande do Sul (RS). The municipality of Pelotas, located in the south part of RS state, is responsible for 90% of peach production having adequate conditions of climate and soil for its production. One of the main problems faced by fruit farmers is the management of the peach orchard, which has been homogeneously managed, without considering the spatial and temporal variability of soil, plant and climate attributes in the peach orchard. Therefore, some aspects deserve attention from researchers, among them we can highlight the knowledge of the physical environment in which the peach tree grows. This work had as objectives: i. to evaluate the relationship between soil hydric-physical and crop attributes through the canonical correlation analysis, ii. to determine the spatial and temporal structures of soil hydric-physical, crop and climate attributes, applying geostatistics analysis. The work was conducted in an experimental area, located in the city of Morro Redondo-RS, cultivated with 18 line peach crops, cv. Esmeralda, totaling 1,450 plants. In this area was established a experimental grid consisted of 101 experimental peach trees. At a distance of 0.50m to the right side of each crop tree, trenches were opened to collect disturbed and undisturbed soil samples to determine the following soil hydric-physical attributes, in the 0.00-0.10m and 0.10-0.20m soil layers: sand, silt and clay contents, soil bulk density, soil total porosity, soil macro- and micro-porosities, and volumetric soil water content. We also evaluated the following peach crop attributes in the years of 2010 and 2011: trunk diameter, size of the fruit/plant, total number of fruits/plant, fresh mass of fruits, fruit firmness, brix content and crop productivity. The attributes of climate air temperature and relative humidity were also evaluated in the peach orchard. All data sets were submitted to descriptive statistical analysis. The correlation between soil and crop attributes was evaluated by canonical correlation analysis. The spatial and temporal variability structures of all data sets were evaluated by geostatistics as well as the relationship between them. Results show that the canonical correlation analysis identified the highest correlation coefficients of soil micro-porosity and clay content variables and peach productivity, and that the geostatistical analysis allowed establishing homogeneous management zones of soil, crop and climate attributes as well as to infer, visually, spatial inter-relationships between variables. The association of soil, crop and climate maps indicates that future differentiated managements of agricultural practices on the peach orchard should be based on the spatial distribution of these variables aiming rational water and fertilizer applications to preserve natural resources in the agricultural farmers.